Negative electrode sheet, secondary battery, and electric device

CN122991981APending Publication Date: 2026-10-27CALB GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611223805.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0002]目前,为了提高电池的能量密度,通常采用负极材料层减薄,正极材料层增厚的方式,但是这种方式会导致锂离子在集流体表面成核时易因局部电场或表面缺陷形成锂枝晶,锂枝晶易与电解液发生界面副反应,导致电池的循环寿命下降

Benefits of technology

本申请通过在负极集流体上设置含有金属有机框架材料的涂层,金属有机框架材料的孔径均一可控,利用金属有机框架材料的纳米孔道能引导锂离子均匀沉积,避免局部聚集,抑制锂枝晶的生成,改善二次电池的循环寿命;本申请通过综合调控涂层的厚度hμm、涂层的电子电导率σS/cm及金属有机框架材料的平均孔径rnm,使h/(σ0.1×r)在适宜范围内,可以在保障锂离子的传输效率的同时,降低电荷转移阻抗,提高电解液对负极片的浸润效果,从而兼顾电池的快充性能和循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a negative plate, a secondary battery and an electric device, and belongs to the technical field of secondary batteries. The negative plate comprises a negative current collector and a coating arranged on at least one side surface of the negative current collector, and the coating comprises a metal organic framework material. The application sets the coating containing the metal organic framework material on the negative current collector, the pore diameter of the metal organic framework material is uniform and controllable, the nano-pore channel of the metal organic framework material is used to guide the uniform deposition of lithium ions, local aggregation is avoided, the generation of lithium dendrites is inhibited, and the cycle life of the secondary battery is improved; the application comprehensively regulates the thickness h of the coating, the electronic conductivity sigma S / cm of the coating and the average pore diameter r of the metal organic framework material, so that h / (sigma 0.1 Xr) is within a suitable range, the lithium ion transmission efficiency can be ensured, the charge transfer impedance is reduced, the impregnation effect of the electrolyte on the negative plate is improved, and the fast-charging performance and the cycle performance of the battery are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary battery technology, specifically to a negative electrode sheet, a secondary battery, and an electrical device. Background Technology

[0002] Currently, in order to improve the energy density of batteries, the negative electrode material layer is usually thinned and the positive electrode material layer is thickened. However, this method can lead to the formation of lithium dendrites when lithium ions nucleate on the surface of the current collector due to local electric field or surface defects. Lithium dendrites are prone to interfacial side reactions with the electrolyte, resulting in a decrease in the cycle life of the battery. Summary of the Invention

[0003] Based on the deficiencies of the existing technology, the purpose of this application is to provide a negative electrode sheet, a secondary battery, and an electrical device.

[0004] To achieve the above objectives, the technical solution adopted in this application is as follows: The first aspect of this application provides a negative electrode sheet, which includes a negative electrode current collector and a coating disposed on at least one surface of the negative electrode current collector. The coating comprises a metal-organic framework material, the coating thickness is h μm, the electronic conductivity of the coating is σ S / cm, and the average pore size of the metal-organic framework material is rn μm. The negative electrode sheet satisfies: h / (σ S / cm) 0.1 ×r) ranges from 0.1 to 44.1.

[0005] A second aspect of this application provides a secondary battery, including the aforementioned negative electrode, as well as a positive electrode, an electrolyte, and a separator.

[0006] A third aspect of this application provides an electrical device including the aforementioned secondary battery.

[0007] Compared with the prior art, the beneficial effects of this application are as follows: This application involves applying a coating containing a metal-organic framework (MOF) material to the negative electrode current collector. The MOF material has a uniform and controllable pore size, and its nanopores guide uniform lithium-ion deposition, preventing localized aggregation, suppressing lithium dendrite formation, and improving the cycle life of the secondary battery. This application achieves this by comprehensively controlling the coating thickness (hμm), electronic conductivity (σS / cm), and average pore size (rnm) of the MOF material, thus achieving a uniform pore size (h / (σS / cm)). 0.1 Within a suitable range, while ensuring the lithium-ion transmission efficiency, the charge transfer impedance can be reduced and the wetting effect of the electrolyte on the negative electrode can be improved, thus balancing the battery's fast charging performance and cycle performance. Detailed Implementation

[0008] To better illustrate the purpose, technical solution, and advantages of this application, the following description, in conjunction with specific embodiments and comparative examples, aims to provide a detailed understanding of the content of this application, rather than to limit it. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this application.

[0009] The technical features described in this application in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions.

[0010] It should be understood that, unless otherwise specified, the numerical ranges involved in this application are considered continuous, including the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the maximum and minimum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed in this application should be understood to include any or all of the subranges to which they are included.

[0011] It should be understood that this application does not impose any particular restrictions on the specific dispersion or mixing methods.

[0012] The first aspect of this application provides a negative electrode sheet, which includes a negative electrode current collector and a coating disposed on at least one surface of the negative electrode current collector. The coating comprises a metal-organic framework material, the coating thickness is h μm, the electronic conductivity of the coating is σ S / cm, and the average pore size of the metal-organic framework material is rn μm. The negative electrode sheet satisfies: h / (σ S / cm) 0.1 ×r) ranges from 0.1 to 44.1.

[0013] The inventors discovered that by applying a coating containing a metal-organic framework (MOF) to the negative electrode current collector, the pore size of the MOF can be uniformly controlled. The nanopores of the MOF can guide the uniform deposition of lithium ions, preventing local aggregation, inhibiting lithium dendrite formation, and improving the cycle life of the secondary battery. However, the MOF-containing coating has poor conductivity; if the coating thickness is too thick, it will cause a decrease in the fast-charging performance of the secondary battery. Improving the electronic conductivity of the coating can enhance its electronic conduction capability, and / or, by increasing the average pore size of the MOF, can improve the wetting effect of the electrolyte on the negative electrode, promoting lithium ion transport and thus improving the battery's fast-charging performance. This application comprehensively controls the coating thickness (hμm), electronic conductivity (σS / cm), and average pore size (rnm) of the MOF, and takes σ... 0.1 This reflects the comprehensive control effect of "thickness transmission resistance, channel wetting ability, and electronic conductivity", making h / (σ 0.1Within a suitable range, while ensuring the lithium-ion transmission efficiency, the charge transfer impedance can be reduced and the wetting effect of the electrolyte on the negative electrode can be improved, thus balancing the battery's fast charging performance and cycle performance.

[0014] For example, h / (σ 0.1 ×r) can be a range of values ​​consisting of any one or any two of the following: 0.1, 0.2, 0.3, 0.38, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 13.2, 13.49, 13.5, 13.8, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 44.1.

[0015] In some implementations, h / (σ) 0.1 ×r) is preferably 0.38~13.49. When h / (σ 0.1 Within this preferred range, the secondary battery exhibits better overall performance (×r).

[0016] In some implementations, hμm is 0.5μm to 8μm.

[0017] For example, hμm can be a numerical range of any one or any two of 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, and 8μm.

[0018] hμm is preferably 1μm~5μm.

[0019] The inventors discovered that, due to the relatively poor conductivity of the coating, adjusting the coating thickness (hμm) to a suitable range helps ensure the battery's fast-charging performance. A coating of suitable thickness also provides sufficient space to induce uniform lithium-ion deposition, reducing lithium dendrite formation and improving the battery's cycle performance.

[0020] The method for preparing the negative electrode sheet includes the following steps: mixing the components of the coating (metal-organic framework material, reinforcing agent and binder) and solvent to prepare a coating slurry, coating the coating slurry onto at least one side surface of the negative electrode current collector, and then drying it.

[0021] This application does not impose any particular restrictions on the means of controlling the coating thickness hμm. The coating thickness hμm can be controlled by adjusting the coating slurry coating thickness; or the coating thickness hμm can be controlled by rolling after drying and adjusting the rolling pressure.

[0022] This application does not impose any particular restrictions on the means of controlling the electronic conductivity σS / cm of the coating.

[0023] For example, the coating includes a reinforcing agent, which includes a fullerene, such as C. 60 C 70 The electronic conductivity σS / cm of the coating can be controlled by adjusting the mass percentage (10-20%) of the reinforcing agent in the coating. The higher the mass percentage of the reinforcing agent in the coating, the higher the electronic conductivity of the coating.

[0024] For example, the electronic conductivity σS / cm of the coating can be controlled by adjusting the ligand selection of the metal-organic framework material. The more conjugated double bond groups in the structural formula of the ligand, the higher the electronic conductivity of the coating.

[0025] For example, the electronic conductivity σS / cm of the coating can be controlled by adjusting the mass percentage of dopant elements in the coating. The higher the mass percentage of dopant elements in the coating, the higher the electronic conductivity of the coating.

[0026] This application also provides means to improve ionic conductivity. For example, the preparation method of the coating further includes immersing the coated negative electrode current collector in a lithium salt solution after drying, and then drying it again. The means to control the ionic conductivity of the coating can be: controlling the ionic conductivity of the coating by adjusting the concentration of lithium salt in the lithium salt solution (0.1~0.5mol / L) and the soaking time (30min~12h).

[0027] This application does not impose any particular limitation on the means of controlling the average pore size (rnm) of metal-organic framework materials. The means of controlling the average pore size (rnm) of the metal-organic framework material include, but are not limited to, controlling the average pore size (rnm) of the metal-organic framework material through ligand selection and / or reaction temperature. The more carbon elements in the ligand's structural formula, the larger the average pore size of the metal-organic framework material; the higher the reaction temperature, the larger the average pore size of the metal-organic framework material.

[0028] In some implementations, σS / cm is 0.001S / cm to 5S / cm.

[0029] For example, σS / cm can be 0.001S / cm, 0.005S / cm, 0.01S / cm, 0.05S / cm, 0.1S / cm, 0.2S / cm, 0.3S / cm, 0.4S / cm, 0.5S / cm, 0.6S / cm, 0.7S / cm, 0.8S / cm, 0.9S / cm, 1.0S / cm, 1.1S / cm, 1.2S / cm, 1.3S / cm, 1.4S / cm, 1.5S / cm, 1.6S / cm, 1.7S / cm, 1.8S / cm, 1.9S / cm, 2.0S / cm, 2.1S / cm, 2.2S / cm, 2.3S / cm, etc. A range of values ​​consisting of any one or any two of the following: 2.4S / cm, 2.5S / cm, 2.6S / cm, 2.7S / cm, 2.8S / cm, 2.9S / cm, 3.0S / cm, 3.1S / cm, 3.2S / cm, 3.3S / cm, 3.4S / cm, 3.5S / cm, 3.6S / cm, 3.7S / cm, 3.8S / cm, 3.9S / cm, 4S / cm, 4.1S / cm, 4.2S / cm, 4.3S / cm, 4.4S / cm, 4.5S / cm, 4.6S / cm, 4.7S / cm, 4.8S / cm, 4.9S / cm, and 5S / cm.

[0030] The preferred value for σS / cm is 0.01S / cm to 2S / cm.

[0031] The inventors discovered through research that by adjusting the electronic conductivity σS / cm of the coating to a suitable range, the charge transfer impedance (Rct) can be reduced, ensuring the fast-charging performance of the battery. At the same time, the rate of lithium ion migration to the negative electrode surface can be controlled, reducing the precipitation of lithium dendrites and improving the cycle performance of the battery.

[0032] In some implementations, rnm is 0.3nm to 5nm.

[0033] The inventors discovered that a smaller average pore size (rnm) in metal-organic framework (MOF) materials reduces the width of the lithium-ion migration path within the MOF, resulting in poor electrolyte wetting, decreased lithium-ion migration efficiency, and reduced fast-charging performance. Conversely, a larger average pore size (rnm) leads to excessive electrolyte wetting of the negative electrode, increasing side reactions between the electrolyte and the negative electrode. This can cause the electrolyte to break down during cycling and continuously consume active lithium, further reducing battery cycle performance. By adjusting the average pore size (rnm) of the MOF material to an appropriate range, sufficient electrolyte wetting of the negative electrode is ensured, improving lithium-ion transport performance and migration efficiency. This also moderately reduces side reactions between the electrolyte and the negative electrode, thereby improving both battery cycle performance and fast-charging performance.

[0034] For example, rnm can be 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.9nm, 2nm, 2.1nm, 2.2nm, 2.3nm, 2.4nm, 2.5nm, 2.6nm, 2. A numerical range consisting of any one or any two of the following: 7nm, 2.8nm, 2.9nm, 3nm, 3.1nm, 3.2nm, 3.3nm, 3.4nm, 3.5nm, 3.6nm, 3.7nm, 3.8nm, 3.9nm, 4nm, 4.1nm, 4.2nm, 4.3nm, 4.4nm, 4.5nm, 4.6nm, 4.7nm, 4.8nm, 4.9nm, and 5nm.

[0035] The preferred rnm is 0.5nm~3nm.

[0036] In some embodiments, the metal-organic framework material contains at least one of carbon-carbon conjugated double bonds and carbon-nitrogen conjugated double bonds. The inventors have discovered that the more conjugated double bond groups a metal-organic framework material contains, the higher the conductivity of the coating.

[0037] In some embodiments, the metal-organic framework material contains at least one of cobalt, zinc, iron, magnesium, aluminum, and copper.

[0038] In some embodiments, the metal-organic framework material includes cobalt, and the cobalt element accounts for 5% to 50% of the coating by mass. The inventors have discovered that a higher content of metal elements in the coating can alter the electronic structure of the metal-organic framework material, thereby significantly improving the conductivity of the coating.

[0039] In some embodiments, the ligands of the metal-organic framework material include at least one selected from porphyrin, phthalocyanine, terephthalic acid, bipyridine, and imidazole.

[0040] In some embodiments, the metal-organic framework material includes at least one of MIL-101, MIL-53, ZIF-7, ZIF-8, and ZIF-67.

[0041] In this application, the preparation method of the metal-organic framework material includes, but is not limited to, the following method: mixing a solution containing a metal salt and a solution containing a ligand, adding triethylamine to obtain a mixed solution, subjecting the mixed solution to a solvothermal reaction, and then centrifuging, washing, and drying to obtain the metal-organic framework material.

[0042] In the above-mentioned method for preparing metal-organic framework materials, the solution containing metal salt includes a metal salt and a solvent, wherein the ratio between the amount of the metal salt and the volume of the solvent is (0.1~1) mmol: 20 mL, and the solvent includes at least one of methanol and N,N-dimethylformamide.

[0043] In the above-mentioned method for preparing metal-organic framework materials, the solution containing ligands includes ligands and solvents, wherein the ratio between the mass of the ligand and the volume of the solvent is (0.1~2) g: 100 mL.

[0044] In the above-mentioned method for preparing metal-organic framework materials, the ratio between the amount of metal salt in the solution containing the metal salt and the amount of ligand in the solution containing the ligand is (1~5):1.

[0045] In the above-mentioned method for preparing metal-organic framework materials, the metal element in the metal salt includes at least one of cobalt, zinc, iron, magnesium, aluminum and copper, and the metal salt can be at least one of nitrate, chloride and sulfate.

[0046] In the above-mentioned method for preparing metal-organic framework materials, the reaction temperature of the solvothermal reaction is 60~200℃ and the reaction time is 6h~48h.

[0047] In some embodiments, the porosity of the coating is 30% to 50%.

[0048] For example, the porosity of the coating can be any one or any combination of 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%.

[0049] Through research, the inventors discovered that by controlling the porosity of the coating within a suitable range, the wetting effect of the electrolyte on the negative electrode can be guaranteed, improving the lithium-ion transport efficiency, enhancing the fast-charging performance of the battery, and preventing excessive wetting of the negative electrode by the electrolyte, which would lead to an aggravation of side reactions, thereby ensuring the cycle performance of the battery.

[0050] In some embodiments, the coating also includes an adhesive.

[0051] In the coating, the sum of the mass percentages of the metal-organic framework material and the reinforcing agent is 94% to 97%, and the mass percentage of the binder is 3% to 6%.

[0052] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, the metal foil may include copper foil. The composite current collector may include a substrate layer and a metal layer formed on at least one surface of the substrate layer; the composite current collector may be obtained by forming a metal material on a polymer substrate; the substrate layer is a polymer material, such as at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE); the metal layer may be made of at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy.

[0053] In this application, the negative electrode sheet can be prepared according to conventional methods in the art. For example, the preparation method of the negative electrode sheet includes the following steps: The components of the coating (metal-organic framework material, reinforcing agent and binder) are dispersed in a solvent to obtain a coating slurry. The coating slurry is applied to at least one surface of the negative electrode current collector, dried and rolled to form a coating on the negative electrode current collector, and then cut to obtain a negative electrode sheet.

[0054] In the above-described method for preparing the negative electrode sheet, the solid content of the coating slurry is 40-70%, the coating method is blade coating, the blade gap is 10-100μm, and the rolling pressure is 20-30 tons.

[0055] A second aspect of this application provides a secondary battery, including the aforementioned negative electrode, as well as a positive electrode, an electrolyte, and a separator.

[0056] In some embodiments, the positive electrode material layer further comprises a positive electrode material, a positive electrode binder, and a positive electrode conductive agent.

[0057] In some embodiments, the thickness of the positive electrode material layer is 100~200μm.

[0058] For example, the thickness of the positive electrode material layer can be any one or any combination of 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm.

[0059] In some embodiments, the thickness ratio of the positive electrode material layer to the negative electrode material layer is 13 to 400.

[0060] For example, the thickness ratio of the positive electrode material layer to the negative electrode material layer can be any one or any two of the following values: 13, 15, 20, 25, 30, 40, 50, 60, 70, 80, 100, 120, 150, 180, 200, 220, 250, 280, 300, 320, 350, 380, and 400.

[0061] In some embodiments, the compaction density of the positive electrode is 2 g / cm³. 3 ~2.8g / cm 3 This application regulates the compaction density of the positive electrode sheet to a suitable range, which can ensure the wetting effect of the electrolyte on the positive electrode sheet, reduce side reactions between the positive electrode sheet and the electrolyte, improve lithium-ion transport efficiency, and improve the cycle performance and fast charging performance of the battery.

[0062] For example, the compaction density of the positive electrode sheet can be 2.0 g / cm³. 3 2.1g / cm 3 2.2g / cm 3 2.3g / cm 3 2.4g / cm 3 2.5g / cm 3 2.6g / cm 3 2.7g / cm 3 2.8g / cm 3 The range of values ​​consisting of any one or any two of them.

[0063] In some embodiments, the sheet resistance of the positive electrode is 10 mΩ·cm to 200 mΩ·cm. This application adjusts the sheet resistance of the positive electrode to a suitable range, which can improve lithium-ion transport efficiency, enhance the fast-charging performance of the battery, limit the insertion / extraction rate of lithium ions in the positive electrode material layer, reduce structural stress in the positive electrode material, and make the positive electrode material particles less prone to particle breakage or phase transition after long-term battery cycling, thereby improving the battery's cycle performance.

[0064] For example, the sheet resistance of the positive electrode can be any one or any combination of two of the following values: 10 mΩ·cm, 20 mΩ·cm, 30 mΩ·cm, 40 mΩ·cm, 50 mΩ·cm, 60 mΩ·cm, 70 mΩ·cm, 80 mΩ·cm, 90 mΩ·cm, 100 mΩ·cm, 110 mΩ·cm, 120 mΩ·cm, 130 mΩ·cm, 140 mΩ·cm, 150 mΩ·cm, 160 mΩ·cm, 170 mΩ·cm, 180 mΩ·cm, 190 mΩ·cm, and 200 mΩ·cm.

[0065] In some embodiments, the positive electrode material layer includes a positive electrode material with a particle size Dv50 of 0.8~1.3μm. The inventors of this application have discovered that a suitable particle size Dv50 for the positive electrode material ensures a suitable transport path for lithium ions in the positive electrode solid phase, thereby guaranteeing the battery's fast-charging performance; it also ensures a suitable specific surface area for the positive electrode material, reducing side reactions between the positive electrode material and the electrolyte, thereby guaranteeing the battery's cycle performance.

[0066] For example, the particle size Dv50 of the cathode material can be any one or any combination of 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm.

[0067] In some embodiments, the cathode material includes a dopant element, comprising at least one of Ti, V, and Al, with a mass content of 1500-8000 ppm. Introducing an appropriate amount of dopant element into the cathode material can stabilize its crystal structure, reduce side reactions between the cathode material and the electrolyte, and prevent excessive dopant element from occupying lithium-ion diffusion channels, thus narrowing the diffusion path and increasing resistance, thereby ensuring the battery's fast-charging performance.

[0068] In some embodiments, the surface of the positive electrode material is provided with a coating layer, the thickness of which is 1 nm to 10 nm.

[0069] For example, the thickness of the coating layer can be any one or any combination of 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, and 10nm.

[0070] In some embodiments, the cathode material includes at least one of lithium manganese iron phosphate, lithium iron phosphate, and nickel-cobalt ternary materials.

[0071] In some embodiments, when the positive electrode material is iron phosphate, h / (σ 0.1 The ratio of (×r) is 1.2~44.1, indicating that the secondary battery has better overall performance.

[0072] In some embodiments, when the positive electrode material is lithium manganese iron phosphate, h / (σ 0.1 The ratio of xr) is 0.1~13.49, indicating that the secondary battery has better overall performance.

[0073] In some embodiments, when the cathode material is a nickel-cobalt ternary material, h / (σ 0.1 The ratio of xr) is 0.38~23.5, indicating that the secondary battery has better overall performance.

[0074] Specifically, the preparation method of lithium iron phosphate includes, but is not limited to, the following methods: The lithium source, iron source, phosphoric acid, doped source and coated source are mixed, ground and dried to obtain composite powder; The composite powder was sintered under an inert atmosphere, then cooled, ground, and sieved to obtain lithium iron phosphate with a coating layer on the surface.

[0075] In the above-mentioned method for preparing lithium iron phosphate, the molar ratio of lithium in the lithium source, iron in the iron source, and phosphorus in the phosphorus source is (1~1.1):1:1, the mass of the dopant element in the doping source is 1500~8000ppm of the theoretical amount of lithium iron phosphate, and the mass of the coating source is 1~10% of the total mass of the raw materials used to prepare lithium iron phosphate.

[0076] In the above-mentioned method for preparing lithium iron phosphate, the lithium source may include at least one of lithium hydroxide, lithium carbonate, and lithium oxalate; the iron source may include ferrous sulfate; the phosphorus source may include at least one of ammonium dihydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate, and phosphoric acid; the doping source may include at least one of hydroxides of doping elements, nitrates of doping elements, sulfates of doping elements, and ammonium salts of doping elements; and the coating source may include at least one of sucrose, glucose, alumina, and zirconium oxide.

[0077] In the above-mentioned method for preparing lithium iron phosphate, the mixed grinding method includes, but is not limited to, at least one of wet ball milling and dry ball milling.

[0078] In the above-mentioned method for preparing lithium iron phosphate, the inert atmosphere includes at least one of nitrogen and argon, and the sintering treatment includes the following process: heating to 300-500°C at 1-10°C / min, holding at that temperature for 2-4 hours, and then heating to 600-800°C at 1-10°C / min and calcining at that temperature for 4-12 hours.

[0079] The preparation methods of the lithium manganese iron phosphate include, but are not limited to, the following methods: Iron source, manganese source, dopant source and water are mixed to prepare a mixed salt solution. The mixed salt solution and a solution containing phosphorus source are added dropwise to the reaction vessel and the pH value is adjusted to 6-7. After reaction, standing and aging, washing and filtering, and drying, FeMnPO4 precursor is obtained. FeMnPO4 precursor, lithium source and coating source are mixed, ground and dried to obtain mixed powder; The mixed powder was sintered under inert gas protection, and then cooled, ground, and sieved to obtain lithium manganese iron phosphate with a coating layer on the surface.

[0080] In the above-mentioned method for preparing lithium manganese iron phosphate, the lithium source may include at least one of lithium hydroxide, lithium carbonate, lithium oxalate, and lithium hydroxide; the iron source may include ferrous sulfate; the phosphorus source may include at least one of ammonium dihydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate, and phosphoric acid; the manganese source may include at least one of manganese nitrate and manganese sulfate; the doping source may include at least one of hydroxide of the doping element, nitrate of the doping element, sulfate of the doping element, and ammonium salt of the doping element; and the coating source may include at least one of sucrose, glucose, alumina, and zirconium oxide.

[0081] In the above-mentioned method for preparing lithium manganese iron phosphate, the molar ratio of iron in the iron source to manganese in the manganese source is x:(1-x), 0<x<1; the ratio between the sum of the amounts of iron in the iron source and manganese in the manganese source, and the amount of lithium in the lithium source to the amount of phosphorus in the phosphorus source is 1:(1~1.05):1; the mass of the dopant element in the doping source is 1500~8000ppm of the theoretical amount of lithium manganese iron phosphate generated; and the mass of the coating source is 1~10% of the total mass of the raw materials used to prepare lithium manganese iron phosphate.

[0082] In the above-mentioned method for preparing lithium manganese iron phosphate, the mixing and grinding method includes, but is not limited to, at least one of wet ball milling and dry ball milling.

[0083] In the above-mentioned method for preparing lithium manganese iron phosphate, the inert atmosphere includes at least one of nitrogen and argon, and the sintering treatment includes the following process: heating to 350-500℃ at 1-10℃ / min, holding at that temperature for 1-4h, and then heating to 650-900℃ at 1-10℃ / min and calcining at a constant temperature for 6-14h.

[0084] The preparation methods of nickel-cobalt ternary materials include, but are not limited to, the following methods: A mixed salt solution containing nickel, cobalt, manganese and dopant sources is prepared by dissolving them in water. The mixed salt solution, precipitant and complexing agent are added to the reaction vessel in a parallel stream. After reaction, the mixture is allowed to stand for aging, filtered, washed and dried to obtain nickel cobalt manganese hydroxide precursor powder. The precursor powder, lithium source, and coating source are mixed and ground to obtain a mixture; The mixture is sintered in an oxidizing atmosphere to obtain a nickel-cobalt-manganese ternary material with a coating layer on the surface.

[0085] In the above-mentioned method for preparing nickel-cobalt-manganese ternary materials, the lithium source may include at least one of lithium hydroxide, lithium carbonate, lithium oxalate, and lithium hydroxide; the nickel source may include at least one of nickel sulfate, nickel chloride, nickel nitrate, and nickel hydroxide; the cobalt source may include at least one of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt hydroxide; the manganese source may include at least one of manganese nitrate, manganese sulfate, manganese hydroxide, and manganese chloride; the doping source may include at least one of hydroxide, chloride, nitrate, sulfate, and ammonium salt of the doping element; the coating source may include at least one of sucrose, glucose, alumina, and zirconium oxide; the precipitant may include at least one of sodium hydroxide solution and potassium hydroxide; and the complexing agent may include ammonia.

[0086] In the above-mentioned preparation method of nickel-cobalt-manganese ternary material, the molar ratio of nickel in the nickel source, cobalt in the cobalt source, and manganese in the manganese source is x:y:z, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1. The ratio between the sum of the molar amounts of nickel in the nickel source, cobalt in the cobalt source, and manganese in the manganese source and the molar amount of lithium in the lithium source is 1:(1~1.05). The mass of the dopant element in the doping source is 1500~8000 ppm of the theoretical amount of nickel-cobalt-manganese ternary material. The mass of the coating source is 1~10% of the total mass of the raw materials used to prepare the nickel-cobalt-manganese ternary material.

[0087] In the above-mentioned preparation method of nickel-cobalt-manganese ternary materials, after the mixed salt solution, precipitant and complexing agent are added to the reaction vessel in parallel, the pH value of the system is 11~12, the concentration of ammonia is 0.5~1mol / L, and the reaction time is 8~16h.

[0088] In the above preparation method of nickel-cobalt-manganese ternary materials, the oxidizing atmosphere is oxygen, and the sintering treatment includes the following process: heating to 400-550℃ at 1-10℃ / min, holding at that temperature for 1-4h, and then heating to 700-1000℃ at 1-10℃ / min and calcining at a constant temperature for 12-24h.

[0089] In some embodiments, the positive electrode conductive agent may include conductive agents conventional in the battery field, such as at least one of conductive carbon black, conductive graphite, graphene, carbon nanotubes, and carbon fibers.

[0090] In some embodiments, the positive electrode binder is used to improve the adhesion between positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. The positive electrode binder may include binders conventional in the battery industry. For example, the positive electrode binder includes at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC), and sodium alginate.

[0091] In this application, based on the total mass of the positive electrode material layer, the mass percentage of the positive electrode active material is 90%~98%, the mass percentage of the positive electrode binder is 1%~5%, and the mass percentage of the positive electrode conductive agent is 1%~5%.

[0092] In some embodiments, the positive electrode includes a positive current collector, at least one surface of which is coated with the positive electrode material layer.

[0093] The positive electrode current collector can be a metal foil or a composite current collector. For example, the metal foil may include aluminum foil. The composite current collector may include a substrate layer and a metal layer formed on at least one surface of the substrate layer. The composite current collector can be obtained by forming a metal material on a polymer substrate. The substrate layer is a polymer material, such as at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE). The metal layer may be made of at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy.

[0094] In this application, the positive electrode sheet can be prepared according to conventional methods in the art, for example, dispersing the components of the positive electrode material layer in a solvent to obtain a positive electrode slurry, coating the positive electrode slurry onto at least one surface of the positive electrode current collector, and then drying, rolling, and cutting to obtain the positive electrode sheet.

[0095] In some embodiments, the viscosity of the electrolyte at 25°C is 1.5 cp to 3.7 cp. The inventors of this application have discovered that adjusting the viscosity of the electrolyte to a suitable range can ensure the lithium-ion transport efficiency, thereby guaranteeing the fast-charging performance of the battery, while also reducing side reactions between the electrolyte and the positive and negative electrodes, thus improving the battery's cycle performance.

[0096] In some embodiments, the electrolyte includes a solvent.

[0097] In some embodiments, the solvent includes at least one selected from carbonate solvents, carboxylic acid ester solvents, ether solvents, sulfone solvents, nitrile solvents, and phosphate ester solvents. The carbonate solvents include dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate; the carboxylic acid ester solvents include at least one selected from methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), and 1,4-butyrolactone (GBL); the ether solvents include at least one selected from ethylene glycol dimethyl ether and tetrahydrofuran; and the sulfone solvents include at least one selected from sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0098] In some embodiments, the electrolyte includes an additive, which includes at least one of vinylene carbonate, vinyl sulfate (DTD), 1,3-propanesulfonate lactone (PS), methanedisulfonate (MMDS), vinylene carbonate (VC), and fluorovinyl carbonate (FEC).

[0099] In some embodiments, the mass percentage of additives in the electrolyte is 1% to 6%. The inventors of this application have discovered that controlling the additives in the electrolyte within a suitable range can promote the formation of an SEI film of appropriate thickness on the negative electrode, avoiding an excessively thick SEI film that would lead to a sharp increase in interfacial impedance. Simultaneously, it reduces side reactions between the electrolyte and the negative electrode, thereby improving the battery's fast-charging and cycle performance.

[0100] In some embodiments, the electrolyte comprises a lithium salt, which includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium difluoromethanesulfonylimide, lithium ditrifluoromethanesulfonylimide, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0101] In some embodiments, the concentration of lithium salt in the electrolyte is 0.5 mol / L to 2 mol / L.

[0102] In some embodiments, the air permeability of the separator is 50s / 100CC to 500s / 100CC. By controlling the air permeability of the separator within the above range, this application can ensure lithium-ion transport efficiency, reduce side reactions at the electrolyte-electrode interface, and thus improve the battery's cycle performance while ensuring fast-charging performance.

[0103] This application does not impose any particular restrictions on the type of diaphragm; any well-known porous diaphragm with good chemical and mechanical stability can be selected.

[0104] In some embodiments, the diaphragm includes a base membrane, and at least one surface of the base membrane is provided with a coating. The base membrane may be made of at least one of polyethylene, polypropylene, and polyamide. The coating may be made of at least one of aramid, polyimide, aluminum oxide, boehmite, titanium dioxide, silicon dioxide, zirconium dioxide, tin dioxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, and magnesium nitride.

[0105] In this application, the method for preparing the secondary battery includes, but is not limited to, the following methods: The positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. The cells are then wound to obtain a bare cell. The bare cell is placed in an aluminum-plastic film shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping processes, a lithium-ion battery is obtained.

[0106] Specifically, the transformation process includes the following stages in sequence: The formation process includes the following stages: Pre-activation stage (SOC 0%-30%): Under the conditions of -10℃ and 0.1~0.4 MPa, crystal nuclei are first formed with a large current (10 mA / cm²), and then the current is switched to a small current (0.1C) for charging until 30% SOC is reached; Main formation stage (SOC 30%-80%): Under conditions of 25~45℃ and 0.4~1.0MPa, charge at 0.3C to 80% SOC; Final stage (SOC 80%-100%): Under conditions of 0.4~1.0MPa, cool down to 0~15℃ at a rate of 0.1~1℃ / min, and then charge at 0.3C to 100% SOC.

[0107] A third aspect of this application provides an electrical device including the aforementioned secondary battery.

[0108] The method for testing the coating thickness h μm is as follows: 1) Use a battery charging and discharging device to discharge the secondary battery under test. Discharge conditions: current 0.33C, cut-off lower limit voltage; disassemble the secondary battery and remove the negative electrode. 2) Obtain cross-sectional SEM of the negative electrode by cutting the CP, and measure the coating thickness hμm using scanning electron microscopy.

[0109] The method for testing the average pore size (rnm) of the metal-organic framework material is as follows: The secondary battery under test was discharged using a battery charging and discharging device. The discharge conditions were: current 0.33C, cutoff lower limit voltage. The secondary battery was disassembled, the negative electrode was removed, and the negative electrode was immersed in DMC (dimethyl carbonate) at room temperature for 30 minutes. It was then removed and dried at room temperature with humidity ≤15%. The coating on the surface of the current collector is scraped off, dried under vacuum at 60°C for 12 hours, and then degassed under vacuum at 120°C for 12 hours. After washing and drying, a powder sample is obtained. A known amount of nitrogen gas was gradually introduced into the sample tube, and the pressure at which adsorption equilibrium was reached was recorded. By calculating the pressure change before and after each gas introduction, the amount of gas adsorbed by the sample at this pressure was obtained (relative pressure (P / P0) range: 1×10⁻⁶). -7 (Up to 0.995); gradually reduce the pressure (in 0.005 intervals), measure the desorption process to obtain a complete isothermal adsorption-desorption curve, and then calculate the average pore size of the sample in rnm.

[0110] The method for testing the electronic conductivity σS / cm of the coating: 1) Use a battery charging and discharging device to discharge the secondary battery under test. Discharge conditions: temperature 25℃, current 0.33C, cutoff condition is the lower limit voltage; disassemble the lithium-ion battery in the discharged state to obtain the negative electrode sheet, and cut the negative electrode sheet into small sample pieces (15mm*15mm). 2) Using the four-probe method, four probes arranged at equal intervals (1mm*1mm) are brought into contact with the sample surface, current is applied and voltage is measured to calculate the conductivity of the sample.

[0111] 4. Test method for coating porosity: Sampling and Preparation: Prepare coated electrode sheets of known dimensions, weigh them, and calculate their apparent total volume (length × width × thickness). Vacuum Impregnation: Place the electrode sheet in a vacuum container, evacuate to a pressure of -0.09 to -0.1 MPa, then inject dimethyl carbonate until the liquid completely penetrates the pores, and then remove it. Weighing and Calculation: Wipe off excess liquid from the surface of the electrode, weigh it, and then calculate the porosity.

[0112] The method for testing the viscosity c mPa / s of the electrolyte at 25°C is as follows: The secondary battery under test was discharged using a battery charging and discharging device under the following conditions: current 0.33C, cutoff voltage limit. Then, the battery was disassembled and the electrolyte collected in a glove box (H2O ≤ 0.1ppm, O2 ≤ 0.1ppm). There are three methods for collecting the electrolyte: After removing the battery cover, ① if there is free electrolyte, collect it into a 5mL sample tube using a pipette and seal it with sealing tape to prevent leakage. ② if there is no free electrolyte, a hydraulic press (Beijing Heng'ao Technology Co., Ltd.'s FY-30 hydraulic press) can be used to continuously pressurize until free electrolyte appears. Collect the electrolyte into a sample tube and seal it. ③ Add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate for 12 hours to allow the electrolyte in the electrode to mix thoroughly with the dichloromethane. Then, use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube and seal the sample tube with sealing glue. The electrolyte was removed and tested using a Cambridge viscometer. The Cambridge viscometer is designed based on electromagnetic oscillation viscosity detection technology, using a magnetically levitated probe for viscosity measurement. Specifically, the electrolyte was placed in a beaker, and the sample temperature was controlled at 25°C for testing. After the displayed value stabilized, the reading was taken and recorded as c.

[0113] The test methods for the mass content of doped element M in the cathode material layer and the mass percentage content of metal elements in the coating are as follows: Discharge the battery to the lower limit voltage (2.5V) at 0.33C, disassemble the empty lithium-ion battery, disassemble the lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, dry it at room temperature with humidity ≤15%, and scrape off the positive electrode material powder on the surface of the current collector. Accurately weigh a certain amount of powder (e.g., 0.2g), disperse it in 20ml of water, add 10ml of nitric acid, mix thoroughly, and heat until the powder dissolves. Then, dilute the mixture to 100mL with water to obtain the test solution. Perform ICP testing on the test solution. Before testing, a standard solution must be prepared. The linear correlation coefficient of the standard concentration must be above 0.999 to be used as a normal standard. Dilute the 1000 mg / L standard solution with deionized water to different concentrations (generally 0, 1 mg / 100mL, 2 mg / 100mL, 3 mg / 100mL), and select the element detection wavelength. Set the experimental conditions: Based on the characteristics of the sample and the element to be detected, set appropriate ICP instrument operating conditions: gas flow rate 0.5L / min, power 1150W, and select the element detection wavelength, which depends on the element being tested (e.g., Fe wavelength 259.94nm, Mn wavelength 257.61nm, Ni wavelength 231.60nm, Mg wavelength 279.08nm). The wavelengths of Al (396.15 nm), Ti (323.452 nm), Zr (336.12 nm), Nb (3094 nm), W (239.7 nm), Co (228.616 nm), and Y (371 nm) can be determined using the self-service analysis function of the ICP testing software. This allows us to read the content of elements in the sample, which is the mass content of doped element M in the cathode material layer. Based on the negative electrode, the coating on the surface of the current collector is deflected, and then the mass percentage of metal elements in the coating is tested according to the steps described above.

[0114] The method for testing the thickness of the coating layer can be: The lithium-ion battery was discharged to 2.5V at 0.33C, and then the positive electrode was disassembled. The positive electrode was dried at 40℃ for 4 hours, and then powder was scraped off. 1g of the powder was dispersed in 100ml of 98% alcohol and stirred for 30min. The dispersed powder was then dropped onto the copper foil on the TEM sample stage and sent into the TEM microscope for testing. The measurement was performed at an appropriate magnification according to different thicknesses. Five different regions were selected for measurement, and the average value was taken.

[0115] 8. Test method for the thickness of the positive electrode material layer: 1) Use a battery charging and discharging device to discharge the secondary battery under test. Discharge conditions: current 0.33C, cut-off lower limit voltage; disassemble the secondary battery and remove the positive electrode. 2) Obtain cross-sectional SEM of the negative electrode sheet by cutting the CP, and measure the thickness of the positive electrode material layer in the positive electrode sheet using scanning electron microscopy.

[0116] The method for testing the particle size Dv50 of the cathode material includes the following steps: (1) Use a battery charging and discharging device to discharge the secondary battery under test. Discharge conditions: current 0.33C, cutoff 2.5V. After recording the battery number / barcode, disassemble the discharged battery in a glove box (molar content of H2O ≤ 0.1ppm, molar content of O2 ≤ 0.1ppm), take out the positive electrode, soak the positive electrode in dimethyl carbonate (DMC) solution at room temperature for 4h, after soaking, take out the positive electrode and dry it in a vacuum environment, and scrape the positive electrode material powder on the surface of the electrode with a ceramic knife; (2) Take 1g of scraped positive electrode material powder as a sample, and use a laser particle size distribution measuring instrument (Mastersizer 3000) to measure the particle size distribution curve according to the particle size distribution laser diffraction method (refer to GB / T19077-2016 for specific steps). In the particle size distribution curve, the particle size value corresponding to the cumulative volume percentage reaching 50% is Dv50.

[0117] The test method for the compaction density of the coating of the positive electrode sheet: Discharge the battery to the lower limit voltage at 0.33C, remove the empty battery, disassemble the positive electrode, soak the electrode in dimethyl carbonate (DMC) solution for 4 hours; then air dry. The pretreated positive electrode sheet is punched into circular sheets of a fixed area using a punching machine. The area is denoted as S0. Three circular sheets are taken as parallel samples, and their masses are weighed using an electronic balance. The average mass is recorded as m1. The thickness of the active material layer (i.e., the total thickness minus the current collector) in each of the three circular sheets is measured using a micrometer. The average mass is recorded as H. Finally, a suitable amount of deionized water is added to each of the three circular sheets, and the coating is gently wiped away with lint-free paper to expose the copper foil. The sheets are then left to stand at room temperature (or dried) for 10 minutes. After the copper foil is dry, the masses of the three copper foil sheets are weighed, and the average mass is recorded as m0. The areal density of the electrode sheet is calculated as (m1-m0) / S0 and the units are converted. This density is denoted as P, where P is in g / cm³. 2 Calculate the P / H ratio and convert the units to obtain the compaction density of the electrode, in g / cm³. 3 .

[0118] The method for testing the surface resistance of the positive electrode: The four-probe method was used for testing, and the testing steps are as follows: Equipment preparation and calibration: Power on and warm up, calibrate with a standard resistance element to ensure accurate probe spacing; Sample placement: Place the positive electrode flat on the test stage, ensuring that the coating surface is smooth and the coating is uniformly in contact with the probe; Parameter settings: Set the current range (1μA ~ 100mA) to ensure the voltage value is within the range; Multi-point measurement: Take at least 6 points evenly on the electrode and measure and record the data.

[0119] The fast-charging performance of the secondary battery can be determined by the following method: The secondary battery is charged at a constant current of 0.33C to the upper limit voltage, and then charged at a constant voltage until the current is less than or equal to 0.05C; then discharged at 0.33C to the lower limit voltage. The above steps are repeated 3 times, and the capacity discharged in the third cycle is taken as the battery discharge capacity. After resting for 10 minutes, discharge the secondary battery at 1C to the lower limit voltage. After resting for 10 minutes, charge the secondary battery at 0.33C to 10% SOC. Then charge the secondary battery at 4C to the upper limit voltage and record the time t0. Then charge in descending order at 0.4C: charge at 3.6C, 3.2C, 2.8C, 2.4C, 2.0C, 1.6C, 1.2C, 0.8C, and 0.4C in sequence. The cutoff condition for each charge is charging to the upper limit voltage. Record the time t1. t1-t0 is the fast charging time.

[0120] The cycle life of the battery is determined by the following method: At 25°C, the secondary battery was subjected to a cycle test according to the following procedure: ① Charge at a constant current rate of 0.33C to the upper limit voltage, and then charge at a constant voltage until the current drops to 0.05C; ② Let stand for 10 minutes; ③ Discharge at a rate of 0.33C to the lower limit voltage; ④ Let stand for 10 minutes; Perform cycle tests according to steps ① to ④ until the capacity of the lithium-ion battery is less than 80% of the initial capacity, and record the number of cycles.

[0121] In this application, the lower limit voltage in the above test is 2.5V, and the upper limit voltage in the above test is 4.25V.

[0122] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments.

[0123] Unless otherwise specified, all experimental reagents and instruments used in this application are commonly used and ordinary reagents and instruments. Unless otherwise specified, all raw materials used in the embodiments and comparative examples of this application are commercially available, and the raw materials used in each parallel experiment are the same.

[0124] Example 1 The embodiment of the lithium-ion secondary battery described in this application includes a method for preparing the lithium-ion secondary battery comprising the following steps: S1, Preparation of the positive electrode S11. Preparation of lithium iron phosphate: Lithium hydroxide monohydrate was used as the lithium source, ferrous sulfate heptahydrate as the iron source, ammonium dihydrogen phosphate as the phosphorus source, titanium nitrate and ammonium metavanadate as doping sources, and sucrose as the carbon coating source. The lithium source, iron source and phosphorus source were weighed according to the molar ratio Li:Fe:P=1.05:1:1. The amount of carbon coating source added was 8% of the total mass of raw materials. The mass ratio of Ti element in titanium nitrate to V element in ammonium metavanadate was 3:1. The sum of the mass of Ti and V elements in the doping source was 4600ppm of the theoretical amount of lithium iron phosphate generated. All raw materials were placed in an agate ball mill jar, and anhydrous ethanol was added as the dispersion medium. The ball-to-material mass ratio was 20:1. The planetary ball mill was wet-milled at 350r / min for 6h to obtain a uniformly mixed suspension slurry. The slurry was transferred to an evaporating dish and pre-evaporated in an 80°C water bath to remove most of the solvent. Then it was placed in a forced-air drying oven and dried at a constant temperature of 110°C for 12 hours to completely remove ethanol and free water. The mixture was then ground and dispersed to obtain the composite precursor powder. The composite precursor powder was evenly spread on an alumina crucible and placed in a tube furnace. High-purity nitrogen gas (flow rate 80 mL / min) was purged throughout the process to create an inert reducing atmosphere. Pre-sintering was first performed: the temperature was increased to 350℃ at 5℃ / min and held for 3 hours to complete ammonium salt decomposition and preliminary carbonization of organic matter; then, the temperature was further increased to 700℃ at 5℃ / min and calcined at a constant temperature for 8 hours to complete the growth of the olivine phase LiFePO4 crystal phase and in-situ carbon coating. After calcination, the furnace was allowed to cool naturally to room temperature. The sintered product is removed, hand-ground in an agate mortar and pestle, and passed through a 200-mesh standard sieve to remove large agglomerated particles; trace iron impurities are removed by magnetic separation, and carbon-coated lithium iron phosphate powder is finally obtained and used as a positive electrode active material.

[0125] S12. The positive electrode active material, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 98:1:1. The solvent NMP is added, and the mixture is stirred under vacuum until the system is homogeneous to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated onto the two opposite surfaces of the positive electrode current collector aluminum foil. The coating machine is then transferred to an oven for drying. After cold pressing, positive electrode material layers are formed on the two opposite surfaces of the positive electrode current collector. Finally, the foil is cut to obtain a positive electrode sheet. The compaction density of the positive electrode sheet is shown in Table 1. S2, Preparation of the negative electrode S21. Preparation of metal-organic framework materials: Terephthalic acid was selected as the ligand. The ligand was dissolved in the organic solvent DMF with a mass ratio of 0.5 g to 100 mL. The solution was ultrasonically treated at 55 °C for 30 min to obtain solution A. The metal salts used are cobalt nitrate and aluminum nitrate, with a molar ratio of 1:0.43. The metal salts are added to a mixed solvent and sonicated for 10 minutes until completely dissolved to obtain solution B. The mixed solvent is a mixture of methanol and DMF in a 1:1 volume ratio. The ratio of the total amount of metal salts to the volume of the mixed solvent is 0.7 mmol: 20 mL. The solutions A and B obtained above were mixed thoroughly, and triethylamine was slowly added dropwise. The volume ratio of triethylamine to the sum of the volumes of solutions A and B was 0.1:10, resulting in a mixed solution. This mixed solution was transferred to a hydrothermal reactor lined with polytetrafluoroethylene (PTFE), sealed, and reacted at a temperature of 127°C (T1) for 36 hours. After the reaction, the mixture was allowed to cool naturally to room temperature. The solid product was collected by centrifugation (8000 rpm, 10 min), and washed five times alternately with DMF (twice) and methanol (three times). The product was then vacuum dried at 80°C for 24 hours to obtain the metal-organic framework material.

[0126] S22. The metal-organic framework material, fullerene C60, and binder PVDF are dispersed in the solvent N,N-dimethylformamide to obtain a coating slurry with a solid content of 42.0%. Based on the total mass of the metal-organic framework material, fullerene C60, and binder, the mass percentage of the metal-organic framework material is denoted as w1, the mass percentage of fullerene C60 is denoted as w2, and the mass percentage of binder is 4%. w1+w2 is 96%, and w2 is 13.1%. The coating slurry is applied to the two opposite surfaces of the negative electrode current collector using a doctor blade with a gap of 16μm. After drying, rolling, and cutting, the negative electrode sheet is obtained. The rolling pressure is 24.6 tons.

[0127] S3. Preparation of electrolyte Ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 30:50:20. Ethylene carbonate is then added and mixed thoroughly. Next, fully dried lithium salt LiPF6 is dissolved by stirring to prepare an electrolyte. The concentration of LiPF6 in the electrolyte is 1 mol / L, and the mass percentage of vinylene carbonate in the electrolyte is 5%. S4. Preparation of the diaphragm Commercially available PE membranes were chosen as the separator. S5. Preparation of lithium-ion secondary batteries The positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. The cells are then wound to obtain a bare cell. The bare cell is placed in an aluminum-plastic film shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion secondary battery is obtained.

[0128] The formation process includes the following stages in sequence: Pre-activation stage (SOC 0%-30%): Under conditions of -10℃ and 0.4MPa, crystal nuclei are first formed using a large current (10 mA / cm²), and then the current is switched to a small current (0.1C) for charging until 30% SOC is reached; Main formation stage (SOC 30%-80%): Under conditions of 45℃ and 0.8MPa, the crystal nuclei are charged to 80% SOC at 0.3C; Final stage (SOC 80%-100%): Under the condition of 0.8MPa, cool down to 10℃ at a rate of 0.5℃ / min, and charge to 100% SOC at 0.3C.

[0129] Examples 2-20 and Comparative Examples 1-4 Examples 2-20 and Comparative Examples 1-4 each provide a secondary battery, the only difference from Example 1 being that some of the preparation process parameters and characteristic parameters of the resulting secondary battery are different.

[0130] In Example 2, the molar ratio of cobalt nitrate to aluminum nitrate in step S21 is 1:0.45, T1 in step S21 is 137°C, w2 in step S22 is 13.7%, the solid content of the coating slurry in step S22 is 47.6%, the gap of the scraper used in step S22 is 33 μm, and the pressure of the roller is 25.1 tons.

[0131] In Example 3, the ligand used in step S21 is 2-methylimidazole, the metal salts used in step S21 are cobalt nitrate and zinc nitrate, the molar ratio between cobalt nitrate and zinc nitrate is 1:0.38, the T1 in step S21 is 113℃, the w2 in step S22 is 11.5%, the solid content of the coating slurry in step S22 is 51.2%, the gap of the scraper used in step S22 is 44μm, and the pressure of the roller is 24.9 tons.

[0132] In Example 4, the ligand used in step S21 is 2-methylimidazole, the metal salts used in step S21 are cobalt nitrate and zinc nitrate, the molar ratio between cobalt nitrate and zinc nitrate is 1:0.34, the temperature T1 in step S21 is 98°C, the w2 in step S22 is 10.4%, the solid content of the coating slurry in step S22 is 53.2%, the gap of the scraper used in step S22 is 50 μm, and the pressure of the roller is 25.2 tons.

[0133] In Example 5, the ligand selected in step S21 is imidazole, the metal salts selected in step S21 are cobalt nitrate and copper nitrate, the molar ratio between cobalt nitrate and copper nitrate is 1:0.33, T1 in step S21 is 90°C, w2 in step S22 is 10.2%, the solid content of the coating slurry in step S22 is 54.4%, the gap of the doctor blade used in step S22 is 53 μm, and the pressure of the roller is 24.7 tons.

[0134] In Example 6, the ligand selected in step S21 is imidazole, the metal salts selected in step S21 are cobalt nitrate and copper nitrate, the molar ratio between cobalt nitrate and copper nitrate is 1:0.34, the temperature of T1 in step S21 is 86°C, the temperature of w2 in step S22 is 10.3%, the solid content of the coating slurry in step S22 is 58.0%, the gap of the doctor blade used in step S22 is 64 μm, and the pressure of the roller is 24.8 tons.

[0135] In Example 7, the molar ratio of cobalt nitrate to aluminum nitrate in step S21 is 1:0.44, T1 in step S21 is 135°C, w2 in step S22 is 13.4%, the solid content of the coating slurry in step S22 is 42.4%, the gap of the scraper used in step S22 is 17μm, and the pressure of the roller is 25.3 tons.

[0136] In Example 8, the ligand selected in step S21 is imidazole, the metal salts selected in step S21 are cobalt nitrate and copper nitrate, the molar ratio between cobalt nitrate and copper nitrate is 1:0.34, the temperature of T1 in step S21 is 86°C, the temperature of w2 in step S22 is 10.2%, the solid content of the coating slurry in step S22 is 57.6%, the gap of the doctor blade used in step S22 is 63 μm, and the pressure of the roller is 25.0 tons.

[0137] In Example 9, the ligand selected in step S21 is imidazole, the metal salts selected in step S21 are cobalt nitrate and copper nitrate, the molar ratio between cobalt nitrate and copper nitrate is 1:0.33, the temperature of T1 in step S21 is 84°C, the temperature of w2 in step S22 is 10.1%, the solid content of the coating slurry in step S22 is 40.8%, the gap of the doctor blade used in step S22 is 12 μm, and the pressure of the roller is 24.5 tons.

[0138] In Example 10, the ligand selected in step S21 is bipyridine, the metal salts selected in step S21 are cobalt nitrate and copper nitrate, the molar ratio between cobalt nitrate and copper nitrate is 1:0.51, the temperature T1 in step S21 is 156°C, the w2 in step S22 is 15.5%, the solid content of the coating slurry in step S22 is 64.8%, the gap of the doctor blade used in step S22 is 84 μm, and the pressure of the roller is 25.2 tons.

[0139] In Example 11, titanium nitrate was used as the dopant source in step S11, and the mass of Ti element in the dopant source was 4600 ppm of the theoretical amount of lithium iron phosphate. The ligand selected in step S21 was porphyrinazine. The molar ratio between cobalt nitrate and aluminum nitrate in step S21 was 1:0.52. The temperature of T1 in step S21 was 166°C. The concentration of w2 in step S22 was 15.8%. The solid content of the coating slurry in step S22 was 40.1%. The gap of the scraper used in step S22 was 10 μm, and the rolling pressure was 25.1 tons.

[0140] In Example 12, in step S11, titanium nitrate is used as the dopant source, and the mass of Ti element in the dopant source is 4600 ppm of the theoretical amount of lithium iron phosphate. In step S21, the ligand selected is porphyrinazine. In step S21, the molar ratio between cobalt nitrate and aluminum nitrate is 1:0.64. In step S21, T1 is 178°C. In step S22, w2 is 19.4%. In step S22, the solid content of the coating slurry is 41.6%. In step S22, the gap of the scraper is 15 μm, and the rolling pressure is 25.4 tons.

[0141] In Example 13, in step S11, titanium nitrate is used as the dopant source, and the mass of Ti element in the dopant source is 4600 ppm of the theoretical amount of lithium iron phosphate generated. In step S21, the molar ratio between cobalt nitrate and aluminum nitrate is 1:0.46. In step S21, T1 is 139°C. In step S22, w2 is 13.9%. In step S22, the solid content of the coating slurry is 41.6%. In step S22, the gap of the scraper is 15 μm, and the rolling pressure is 24.7 tons.

[0142] In Example 14, in step S11, titanium nitrate is used as the doping source, and the mass of Ti element in the doping source is 4600 ppm of the theoretical amount of lithium iron phosphate. In step S21, the ligand selected is imidazole. In step S21, the metal salts selected are cobalt nitrate and copper nitrate, and the molar ratio between cobalt nitrate and copper nitrate is 1:0.33. In step S21, T1 is 80°C. In step S22, w2 is 10.1%. In step S22, the solid content of the coating slurry is 67.6%. In step S22, the gap of the scraper is 93 μm, and the rolling pressure is 24.8 tons.

[0143] In Example 15, in step S11, titanium nitrate is used as the doping source, and the mass of Ti element in the doping source is 4600 ppm of the theoretical amount of lithium iron phosphate. In step S21, the ligand selected is imidazole. In step S21, the metal salts selected are cobalt nitrate and copper nitrate, and the molar ratio between cobalt nitrate and copper nitrate is 1:0.33. In step S21, T1 is 84°C. In step S22, w2 is 10.0%. In step S22, the solid content of the coating slurry is 69.7%. In step S22, the gap of the scraper is 100 μm, and the rolling pressure is 24.9 tons.

[0144] In Example 16, in step S11, titanium nitrate is used as the doping source, and the mass of Ti element in the doping source is 4600 ppm of the theoretical amount of lithium iron phosphate. In step S21, the ligand selected is imidazole. In step S21, the metal salts selected are cobalt nitrate and copper nitrate, and the molar ratio between cobalt nitrate and copper nitrate is 1:0.52. In step S21, T1 is 84°C. In step S22, w2 is 16.0%. In step S22, the solid content of the coating slurry is 65.6%. In step S22, the gap of the scraper is 87 μm, and the rolling pressure is 25.2 tons.

[0145] In Example 17, the ligand used in step S21 is porphyrinazine, the molar ratio of cobalt nitrate to aluminum nitrate in step S21 is 1:0.63, T1 in step S21 is 164°C, w2 in step S22 is 19.1%, the solid content of the coating slurry in step S22 is 40.8%, the gap of the doctor blade used in step S22 is 12 μm, and the pressure of the roller is 29.9 tons.

[0146] In Example 18, the ligand used in step S21 is porphyrinazine, the molar ratio of cobalt nitrate to aluminum nitrate in step S21 is 1:0.62, T1 in step S21 is 166°C, w2 in step S22 is 18.9%, the solid content of the coating slurry in step S22 is 41.2%, the gap of the scraper used in step S22 is 14 μm, and the pressure of the roller is 20.3 tons.

[0147] In Example 19, the sum of the mass of Ti and V elements in the doping source used in step S11 is 1500 ppm of the theoretical amount of lithium iron phosphate generated. The ligand selected in step S21 is porphyrinazine. The molar ratio between cobalt nitrate and aluminum nitrate in step S21 is 1:0.61. The temperature of T1 in step S21 is 172°C. The temperature of w2 in step S22 is 18.7%. The solid content of the coating slurry in step S22 is 40.8%. The gap of the scraper used in step S22 is 12 μm, and the rolling pressure is 24.8 tons.

[0148] In Example 20, the total mass of Ti and V elements in the doping source used in step S11 is 8000 ppm of the theoretical amount of lithium iron phosphate generated. The ligand used in step S21 is porphyrinazine. The molar ratio of cobalt nitrate to aluminum nitrate in step S21 is 1:0.61. The temperature of T1 in step S21 is 170°C. The concentration of w2 in step S22 is 18.5%. The solid content of the coating slurry in step S22 is 40.8%. The gap of the scraper used in step S22 is 12 μm, and the rolling pressure is 24.9 tons.

[0149] In Example 21, the ligand used in step S21 is porphyrin, the molar ratio of cobalt nitrate to aluminum nitrate in step S21 is 1:0.33, T1 in step S21 is 185°C, w2 in step S22 is 10.0%, the solid content of the coating slurry in step S22 is 39.6%, the gap of the scraper used in step S22 is 9 μm, and the pressure of the roller is 25.2 tons.

[0150] In Example 22, the ligand selected in step S21 is imidazole, the metal salts selected in step S21 are cobalt nitrate and copper nitrate, the molar ratio between cobalt nitrate and copper nitrate is 1:0.68, the temperature of T1 in step S21 is 77°C, the temperature of w2 in step S22 is 20.7%, the solid content of the coating slurry in step S22 is 71.2%, the gap of the doctor blade used in step S22 is 104 μm, and the pressure of the roller is 25.3 tons.

[0151] In Comparative Example 1, the ligand used in step S21 was imidazole, the metal salts used in step S21 were cobalt nitrate and copper nitrate, the molar ratio of cobalt nitrate to copper nitrate was 1:0.33, the temperature of T1 in step S21 was 82℃, the temperature of w2 in step S22 was 10.0%, the solid content of the coating slurry in step S22 was 69.2%, the gap of the doctor blade used in step S22 was 98μm, and the pressure of the roller was 24.8 tons.

[0152] In Comparative Example 2, the ligand used in step S21 was porphyrinazine, the molar ratio of cobalt nitrate to aluminum nitrate in step S21 was 1:0.62, T1 in step S21 was 174℃, w2 in step S22 was 19.0%, the solid content of the coating slurry in step S22 was 40.0%, the gap of the scraper used in step S22 was 10μm, and the pressure of the roller was 24.9 tons.

[0153] In Comparative Example 3, the ligand used in step S21 was imidazole, the metal salts used in step S21 were cobalt nitrate and copper nitrate, the molar ratio between cobalt nitrate and copper nitrate was 1:0.33, the temperature of T1 in step S21 was 77℃, the temperature of w2 in step S22 was 10.1%, the solid content of the coating slurry in step S22 was 71.2%, the gap of the doctor blade used in step S22 was 104μm, and the pressure of the roller was 25.0 tons.

[0154] In Comparative Example 4, the ligand used in step S21 was porphyrinazine, the molar ratio of cobalt nitrate to aluminum nitrate in step S21 was 1:0.64, T1 in step S21 was 162℃, w2 in step S22 was 19.6%, the solid content of the coating slurry in step S22 was 39.6%, the gap of the doctor blade used in step S22 was 9μm, and the pressure of the roller was 25.4 tons.

[0155] The characteristic parameters of the secondary batteries obtained from the above embodiments and comparative examples are shown in Table 1.

[0156] The cycle count and fast charging performance of the secondary batteries obtained in the above embodiments and comparative examples are shown in Table 1.

[0157] Table 1 As can be seen from Table 1, the embodiments of this application, by comprehensively controlling the coating thickness hμm, the electronic conductivity σS / cm, and the average pore size rnm of the metal-organic framework material, achieve h / (σ 0.1 Within a suitable range, while ensuring lithium-ion transport efficiency, charge transfer resistance can be reduced, and the wetting effect of the electrolyte on the negative electrode can be improved. This balances the battery's fast-charging and cycle performance, ensuring a fast-charging time of no more than 34.6 minutes and a cycle count of no less than 509. When h / (σ) 0.1 When the ratio of ×r) is 0.38 to 13.49, the overall improvement in fast charging performance and cycle performance of secondary batteries is better.

[0158] Compared with the embodiments, in Comparative Example 1, h / (σ 0.1 If the ×r value is too high, the fast charging performance of the secondary battery will decrease significantly.

[0159] Compared with the embodiments, in Comparative Example 2, h / (σ 0.1 If the ×r value is too small, the cycle performance of the secondary battery will decrease significantly.

[0160] Compared to the embodiments, in Comparative Example 3, r is too small, h / (σ) 0.1 If the ×r value is too large, the fast charging performance of the secondary battery will decrease significantly, even worse than that of Comparative Example 1.

[0161] Compared with the embodiments, in Comparative Example 4, h is too small, σ is too large, and h / (σ) 0.1 If the ×r) is too small, the cycle performance of the secondary battery will decrease significantly, even worse than that of Comparative Example 2.

[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A negative electrode sheet, characterized in that, The device includes a negative electrode current collector and a coating disposed on at least one surface of the negative electrode current collector. The coating comprises a metal-organic framework material, the coating thickness is h μm, the electronic conductivity of the coating is σ S / cm, and the average pore size of the metal-organic framework material is rn μm. The negative electrode sheet satisfies: h / (σ S / cm) 0.1 ×r) ranges from 0.1 to 44.

1.

2. The negative electrode sheet as described in claim 1, characterized in that, h / (σ 0.1 The value of (×r) ranges from 0.38 to 13.

49.

3. The negative electrode sheet as described in claim 1, characterized in that, hμm is 0.5μm~8μm, and / or σS / cm is 0.001S / cm~5S / cm, and / or rnm is 0.3nm~5nm.

4. The negative electrode sheet as described in claim 1, characterized in that, The metal-organic framework material contains at least one of carbon-carbon conjugated double bonds and carbon-nitrogen conjugated double bonds.

5. The negative electrode sheet as described in claim 1, characterized in that, The metal-organic framework material contains at least one of cobalt, zinc, iron, magnesium, aluminum, and copper.

6. The negative electrode sheet as described in claim 5, characterized in that, The metallic element includes cobalt, and the mass percentage of cobalt in the coating is 5% to 30%.

7. The negative electrode sheet as described in claim 1, characterized in that, The ligands of the metal-organic framework material include at least one of porphyrin, phthalocyanine, terephthalic acid, imidazole and its derivatives.

8. The negative electrode sheet as described in claim 1, characterized in that, The metal-organic framework material includes at least one of MIL-101, MIL-53, ZIF-7, ZIF-8, and ZIF-67.

9. The negative electrode sheet as described in claim 1, characterized in that, The porosity of the coating is 30% to 50%.

10. A secondary battery, characterized in that, The device includes the negative electrode sheet as described in any one of claims 1 to 9, and further includes the positive electrode sheet, the separator, and the electrolyte.

11. The secondary battery as described in claim 10, characterized in that, The thickness of the positive electrode material layer is 100~200μm.

12. The secondary battery as described in claim 10, characterized in that, The thickness ratio of the positive electrode material layer to the coating in the negative electrode sheet is 13~400.

13. The secondary battery as described in claim 10, characterized in that, The compaction density of the positive electrode is 2 g / cm³. 3 ~2.8g / cm 3 .

14. The secondary battery as described in claim 10, characterized in that, The sheet resistance of the positive electrode is 10 mΩ·cm to 200 mΩ·cm.

15. The secondary battery as described in claim 10, characterized in that, The positive electrode material layer includes a positive electrode material, and the particle size Dv50 of the positive electrode material is 0.8~1.3μm.

16. The secondary battery as described in claim 15, characterized in that, The cathode material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, and nickel-cobalt ternary materials.

17. The secondary battery as described in claim 16, characterized in that, When the positive electrode material is iron phosphate, h / (σ 0.1 ×r) is 1.2~44.1; Alternatively, when the cathode material is lithium manganese iron phosphate, h / (σ 0.1 ×r) ranges from 0.1 to 13.49; Alternatively, when the cathode material is a nickel-cobalt ternary material, h / (σ 0.1 The value of (×r) ranges from 0.38 to 23.

5.

18. The secondary battery as described in claim 15, characterized in that, The surface of the positive electrode material is provided with a coating layer, the thickness of which is 1 nm to 10 nm.

19. The secondary battery as described in claim 10, characterized in that, The cathode material layer includes a doping element, which includes at least one of Ti, V, and Al, and the mass content of the doping element in the cathode material layer is 1500~8000 ppm.

20. The secondary battery as described in claim 10, characterized in that, The viscosity of the electrolyte at 25°C is 1.5cp to 3.7cp.

21. The secondary battery as described in claim 10, characterized in that, The electrolyte includes additives; The additive includes at least one of vinylene carbonate, vinyl sulfate, 1,3-propanesulfonate lactone, methanedisulfonate, vinylene carbonate, and fluorovinyl carbonate, and / or the mass percentage of the additive in the electrolyte is 1% to 6%.

22. The secondary battery as described in claim 10, characterized in that, The air permeability of the diaphragm is 50s / 100CC to 500s / 100CC.

23. An electrical appliance, characterized in that, Includes the secondary battery as described in any one of claims 10 to 22.